Pengaruh bantuan kredit usaha rakyat PT. Bank Syariah Indonesia tbk. kantor cabang pembantu peukan kota terhadap tingkat pendapatan usaha mikro kecil dan menengah - Nazirah, Anna; Chairiyaton, Chairiyaton (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The existence of MSMEs is very useful to support or increase people's income. Therefore, it is important for the government to contribute properly in supporting and empowering MSMEs to be increased, one of which is financing support in the People's Business Credit program in Islamic banking, including at Bank Syariah Indonesia. This study aims to determine the effect of distribution of People's Business Credit on the income level of MSMEs. The population in this study amounted to 200 people and 67 people were taken as a sample using the slovin formula. This type of research uses a quantitative method, the analysis used is a simple regression test, t test, and the coefficient of determination using SPSS 25. The results of the research conducted show that the t-count value is 4.299 > t-table is 1.997 with a significance of 0.000 <0.05 thus Ho is rejected and Ha is accepted, meaning that KUR distribution has a positive and significant effect on the income level of MSMEs.